Politeness strategies in Oprah Winfred’s talk show “Adele one night only “: gender and cultural pragmatics study - Surjowati, Ribut; Kusnowati, Siti (Universitas Negeri Semarang, 2024)
The purpose of this paper is analyzing the types of politeness strategies employed by Oprah Winfred (OW) in her interview with Adel, a famous American singer, in her program called Adele One Night Only. it is descriptive qualitative study within the framework of pragmatic study. 12 data were obtained from YouTube which presented a talk show entitled “Adele One Night Only” hosted by Oprah Winfrey. The data were analysed using Brown’s and Levinson’s (1987) theory of politeness. The analysis started by exploring the forms of negative politeness from the host’s utterances, and continued to the forms of negative politeness. In each of the analysis, the writer explained the host’s hidden purposes and the expectations from the interviewee and the correlation between gender, culture and types of politeness strategies used from the point of communication aims and cultural values.The findings shows that OW used positive politeness with eight different strategies and negative politeness with 4 different strategies. The politeness strategies employed by OW were meant to build friendly and warm communication as if they are intimate friends and these findings support the theory that most women like talking which aims to keep in touch, especially with friends and relatives.